Small scale green infrastructure design to meet different urban hydrological criteria. (15th April 2016) - Jia, Z.; Tang, S.; Luo, W.; Li, S.; Zhou, M.
Abstract: As small scale green infrastructures, rain gardens have been widely advocated for urban stormwater management in the contemporary low impact development (LID) era. This paper presents a simple method that consists of hydrological models and the matching plots of nomographs to provide an informative and practical tool for rain garden sizing and hydrological evaluation. The proposed method considers design storms, infiltration rates and the runoff contribution area ratio of the rain garden, allowing users to size a rain garden for a specific site with hydrological reference and predict overflow of the rain garden under different storms. The nomographs provide a visual presentation on the sensitivity of different design parameters. Subsequent application of the proposed method to a case study conducted in a sub-humid region in China showed that, the method accurately predicted the design storms for the existing rain garden, the predicted overflows under large storm events were within 13–50% of the measured volumes. The results suggest that the nomographs approach is a practical tool for quick selection or assessment of design options that incorporate key hydrological parameters of rain gardens or other infiltration type green infrastructure. The graphic approach as displayed by the nomographs allow urban planners to demonstrate the hydrological effect of small scale green infrastructure and gain more support for promoting low impact development. Graphical abstract: Nomographs for rain gardens design and performance evaluation. The plots display the relationships of a) p – i(T ), b) I – i(s), c) I – I′(k), and d) h–I′(T), where p is the recurrence interval, I is the rainfall intensity, T is the storm duration, s is the area ratio, I′ is the surplus inflow rate, k is the infiltration capacity, and h is the rain garden depth. Highlights: Analytical approach was developed for design and evaluation for Low Impact Development practices. Nomographs graphically display the design, evaluation processes, and sensitivity of design parameters. Application provides flexibility for rain gardens design and similar stormwater measures.